Genome sequencing and analysis of isolates of Cytospora sorbicola and Cytospora plurivora associated with almond and peach canker - Tawanda E. Maguvu; Rosa J. Frias; Florent P. Trouillas (PLoS ONE, 2025)
Cytospora sorbicola and C. plurivora are significant canker pathogens that affect stone fruits and several other woody plants, severely limiting orchard productivity and longevity. These pathogens are challenging to control, and once established, there is no cure. Therefore, breeding for resistance is the most promising strategy to mitigate their impact. The first step in this process is understanding the interactions between the plants and the pathogens. To facilitate this understanding, we present genome sequencing and analysis of two isolates of C. sorbicola and two isolates of C. plurivora . The genomes of the C. plurivora isolates were assembled to a mean size of 38.4 ± 0.275 Mbp, with a mean guanine-cytosine (GC) content of 51.02 ± 0.25%. In contrast, the genomes of C. sorbicola were assembled to a mean size of 40.48 ± 0.11 Mbp, with a GC content of 50.28 ± 0.1%. The predicted number of protein coding genes for C. plurivora and C. sorbicola isolates was 9,878 ± 17.5 and 10,161 ± 34.5, respectively. Our genome mining efforts focused on identifying putative virulence determinants. We describe the distribution of identified secreted carbohydrate-active enzymes (CAZymes), transporters, cytochrome P450 monooxygenases, proteases, and genes encoding proteins involved in secondary metabolite synthesis. Additionally, we predicted potential effector proteins associated with these isolates. Gene Ontology analysis revealed a higher prevalence of transporter and peptidase activities, indicating an evolutionary adaptation to low pH and nutrient-limited environments. Although the primary aim of this study was to present the genome sequences, a phylogenomic analysis based on conserved single-copy gene sequences strongly suggests that C. paraplurivora is a species of C. plurivora . Therefore, we recommend amending the classification of C. paraplurivora sp. nov. (Ilyukhin et al. 2023) to C. plurivora . Most importantly, we present high-quality genome assemblies for C. sorbicola and C. plurivora isolates, which are critical resources for future studies on plant-pathogen interactions.